1995
DOI: 10.1039/p29950000595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orbital studies of novel N to C migrations in N,N-bisheteroatom-substituted amides—HERON rearrangements

Abstract: Bisheteroatom-substituted amides (R-CO-NXY) can undergo a novel rearrangement of the more electronegative atom from nitrogen t o the carbonyl carbon producing acyl derivatives (R-CO-X) and substituted nitrenes (N-Y). Such reactions have been observed chemically. A M 1 molecular orbital calculations o n N-substituted acetamides support the concerted nature of this process and predict that amino substituents (Y = NR,)promote the rearrangement of similarly or more electronegative nitrogen substituents (X = NR, , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…These rearrangement processes are characterized by a transition state in which the alkoxyl group migrates from the amide nitrogen to the carbonyl carbon (Fig. 5a) and therefore involves heteroatom rearrangements on nitrogen, the HERON reaction 3 (2). Thus, the HERON reaction, as well as the unique properties of N-acyloxy-N-alkoxyamides, can be ascribed to the configuration at nitrogen, namely bisheteroatom substitution.…”
Section: N-alkoxyhydroxamic Acids 4 and A Variety Of Secondary Producmentioning
confidence: 99%
See 3 more Smart Citations
“…These rearrangement processes are characterized by a transition state in which the alkoxyl group migrates from the amide nitrogen to the carbonyl carbon (Fig. 5a) and therefore involves heteroatom rearrangements on nitrogen, the HERON reaction 3 (2). Thus, the HERON reaction, as well as the unique properties of N-acyloxy-N-alkoxyamides, can be ascribed to the configuration at nitrogen, namely bisheteroatom substitution.…”
Section: N-alkoxyhydroxamic Acids 4 and A Variety Of Secondary Producmentioning
confidence: 99%
“…This reaction, though published in the early 1990s, was named in the literature in a 1995 paper in which we presented a semiempirical molecular orbital treatment of the HERON reactions of a range of anomeric amides (2). AM1 predicted, adequately, the ground-state properties of various anomeric amides, as well as the relative propensity for HERON migration of a variety of geminal heteroatom substituents on nitrogen.…”
Section: Computational Verification Of the Heron Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of amines, the resultant anomeric N-amino-N-alkoxyamides are unstable and undergo a novel rearrangement leading to the generation of esters and 1,1-diazenes, the so-called HERON reaction. 7,[10][11][12][13] Recent results have indicated that the mutagens are also susceptible to bimolecular reactions with the cellular conjugating agent glutathione and azide.…”
Section: Introductionmentioning
confidence: 99%